Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Hierarchical Cu Ni micro-nanocone arrays as stable lithium metal hosts - Qiulong Tang; Guang Jiang; Jilu Zhao; Qingyu Dong; Jingshu Wang; Haiyang Zhang; Jianxin Ou; Xuechun Wang; Rong Huang; Hui Shao; Jun Ge; Xuefeng Gao; et al. (Chemical Engineering Journal, 2026)

Cofactor-coupled cytochrome P450 engineering enables high-level biosynthesis of asiatic acid in Saccharomyces cerevisiae - Yuan Zhu; Xiaoguang Yan; Weiguo Li; Yuan Zhong; Jianjun Qiao; Guang-Rong Zhao (Bioresource Technology, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Harnessing soybean okara for enhanced microbial production of indigoidine - Ziqiang Chen; Wenqing Liu; Shenyi Zhang; Yushen Song; Zixuan Zhang; Guanning Yao; Guang-Rong Zhao; Hongji Zhu; Di Zhang; Jianjun Qiao; Hui Zhao; Jiaheng Liu (Bioresource Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Inhibitory effects of different plant extracts on Histomonas meleagridis in vitro and in vivo in chickens - Qiao-Guang Chen; Shuang Wang; Jie Rong; Chen Chen; Zhao-Feng Hou; Dan-Dan Liu; Jian-Ping Tao; Jin-Jun Xu (Veterinary Parasitology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Characteristics of bacterial community structure in the sediment of Chishui River (China) and the response to environmental factors - Fei Di; Donghui Han; Guang Wang; Wenbo Zhao; Daokun Zhou; Nan Rong; Shou Yang (Journal of Contaminant Hydrology, 2024)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Reconstruction method of irregular seismic data with adaptive thresholds based on different sparse transform bases - Hu Zhao; Tun Yang; Yu-Dong Ni; Xing-Gang Liu; Yin-Po Xu; Yi-Lei Zhang; Guang-Rong Zhang (Applied Geophysics, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Multiple metal(loid)s bioaccessibility from cooked seafood and health risk assessment - Wen Liao; Wenbo Zhao; Ye Wu; Nan Rong; Xiaowei Liu; Kaiming Li; Guang Wang (Environmental Geochemistry and Health, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Effects of enhanced ultraviolet-B radiation, water deficit, and their combination on UV-absorbing compounds and osmotic adjustment substances in two different moss species - Rong Hui; Ruiming Zhao; Guang Song; Yixuan Li; Yang Zhao; Yanli Wang (Environmental Science and Pollution Research, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

A new pyridine alkaloid from Zingiberis rhizoma - Feng Shao; Ding-qing Wang; Wei Xiong; Pu-zhao Zhang; Guang-qiang Ma; Rong-hua Liu; Xue-lian Yao (Natural Product Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Selenium and Iodine Levels in Subjects with Kashin-Beck Disease: a Meta-analysis - Lei Yang; Guang-hui Zhao; Fang-fang Yu; Rong-qiang Zhang; Xiong Guo (Biological Trace Element Research, 2016)

Seroprevalence and molecular detection of Mycoplasma ovipneumoniae in goats in tropical China - Guang Rong; Jun-Ming Zhao; Guan-Yu Hou; Han-Lin Zhou (Tropical Animal Health and Production, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Gene mapping related to yellow green leaf in a mutant line in rice (Oryza sativa L.) - Peng Du; Ying-Hua Ling; Xian-Chun Sang; Fang-Ming Zhao; Rong Xie; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)